Inscription of the ’Ukiri’ Serang as Epigraphic Archives of the Old Al-Hilal Katangka Mosque - Ali, St Maisyah Nur; Nuraeni, Nuraeni; Mirwan, Mirwan (Journal Social Civilecial, 2026)
The Al-Hilal Katangka Old Mosque is one of the important Islamic heritages in South Sulawesi which contains a number of inscriptions in the Serang script (ukiri’ serang) on ​​the doors and pulpit of the mosque. Previous studies generally place these inscriptions as a complement to the historical narrative of the mosque, while their function as a primary source for reconstruction of the history of development has not received much attention. This research aims to analyze the function of inscriptions as epigraphic archives in reconstructing the history of mosque construction and renovation. This research uses analytical-descriptive methods with epigraphic and historical approaches. Data was obtained through interviews, direct observation of the inscriptions on the mosque doors and pulpits, visual documentation, transliteration of ukiri’serang into Latin letters, as well as literature studies of historical sources for the Kingdom of Gowa and the development of the Al-Hilal Katangka Old Mosque. Data analysis was carried out through the stages of epigraphic reading, source criticism, historical interpretation, and reconstruction of development chronology based on the information contained in the inscription. The research results show that the Ukiri’ Serang inscription functions as an epigraphic archive which stores information regarding the chronology of development, renovation actors, and memories of the reign of the Gowa Kingdom. The concept of epigraphic archives offered in this research broadens the understanding of the function of inscriptions from simply being a medium of information to being an instrument for storing historical memory which enables a more comprehensive reconstruction of the history of the construction of the Al-Hilal Katangka Old Mosque.